EFFECTS OF NMDA RECEPTOR ANTAGONISTS ON ACUTE POSTOPERATIVE PAIN - Stojanovic, Maja Z; Stevanovic, Predrag; Vuckovic, Sonja; Savic Vujovic, Katarina (Medical Research, 2025)
Introduction/Aim of the paper: Pain represents a multifactorial process with detrimental effects on the entire organism. This randomized, open-label pilot study investigated the effect of preemptive administration of ketamine and magnesium-sulfate on the intensity of postoperative pain after laparoscopic colon tumor resection. Methods: Sixty patients were randomized into the ketamine-magnesium (KM) and the control (C) groups. After the introduction to anesthesia, patients in the KM group received an i.v. bolus dose of 0.5 mg/kg ketamine, followed by a continuous infusion of 0.6 mg/kg/h lasting until the end of surgery. After a bolus dose of ketamine, they received magnesium-sulfate 20 mg/kg in an intravenous infusion (5-10 minutes). Group C received only 0.9% NaCl infusion. After the patients were awakened (0h), the pain intensity was compared (0- 46h) between the two groups. Results: The Mann-Whitney test implied significantly (p<0.05) lower visual analog scale (VAS) scores, in KM group at 0, 1, 2, 10, 22 and 30 hours after the surgery, and no statistical significance (p>0.05) for VAS scores after 6, 14, 18, 38 and 46 hours, compared to C group. Ketamine and magnesium-sulfate significantly (p<0.05) reduced the postoperative consumption of analgesics, increased the sedation level at 0h postoperatively, and increased the overall patient satisfaction with the treatment. Conclusion: Preemptive administration of ketamine and magnesium-sulfate combination has beneficial effect on postoperative pain after laparoscopic colon tumor resection.